Description of the mature larva and pupa of Synchroa chinensis Nikitsky, 1999 (Coleoptera, Synchroidae) - Jiang, Ri-Xin; Huang, Xiu-Dong; Yang, Lin; Chang, Zhi-Min; Long, Jian-Kun; Chen, Xiang-Sheng (Zootaxa, 2022)
During our field work, a series of larvae of the family Synchroidae was collected under the bark of dead trees. Subsequently, most larvae were reare to adults in a lab and were identified as Synchroa chinensis Nikitsky, 1999. In the present paper, we describe the mature larva and pupa of S. chinensis for the first time.